A concentric/ eccentric knee extension/flexion protocol until exhaustion - Pilot Studie - Sousa, M.; Brito, J.; Carvalho, P.; Guimaraes, J. T.; Teixeira, V. H.; Soares, J. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
The aim of this study was to test if a protocol until exhaustion on an isokinetic dynamometer is intense enough to induce alterations in muscle functional and biochemical variables and monitor these alterations for 24 h. Methods: Six trained male participants (25.2±7.0 years; 176.2±6.8 cm; 70.0 kg, 65-94 kg) completed 3 maximal eccentric repetitions at a constant angular velocity of 60°/s to determine the maximal peak torque of the knee extensors (PTE). Afterwards, a exhaustion protocol was conducted which consisted of 3 bouts of a concentric/eccentric knee extension/flexion exercise at 60°/s with a 200-sec rest time between sets. The 1st and 2nd sets were composed by 100 repetitions; in the 3rd set, subjects performed n repetitions until the PTE of 3 consecutive repetitions fall below 25% of the initial value. The range of motion was from 50° to 110° flexion in the knee (0º = full knee extension). Maximal eccentric PTE was also determined after the exhaustion protocol to evaluate force decrease. Blood samples were collected before (moment 1), 2 h (moment 2) and 24 h (moment 3) after the exhaustion protocol and analysed for lactate dehydrogenase (LDH), creatine kinase (CK), C-reactive protein (CRP) and aspartate aminotransferase (AST). A visual analogue scale (VAS; 0-100) was used to determine the delayed onset muscle soreness (DOMS) before the exercise, immediately after, and 2 and 24 h after the protocol. Data were analyzed by one-way repeatedmeasures ANOVA and by paired sample t-test. One participant was excluded from data analysis due to high initial value of CK (622 U/L). Results: There were significant changes in LDH levels with the exercise protocol (p=0.010), being the differences between moments 1 and 2 (165.8±14.7 vs. 193.4±16.1 U/L; p=0.009). There was no significant changes in serum CK activity (p=0.077). No differences were found for AST (p=0.063), and for CRP (p=0.173). There was a significant decrease of the eccentric PTE after the protocol (352.0±57.1 vs. 181.1±61.4 N m; p=0.007). For DOMS (p<0.001), differences where found between the reported values before and immediately after the protocol (2.0±4.5 vs. 64.4±22.6; p=0.039) and before the protocol and 24 h after (2.0±4.5 vs. 48.8±12.3; p=0.003). Discussion: Taking into account that there were significant changes in LDH, DOMS and eccentric PTE, it can be concluded that this exhaustion protocol is capable of inducing muscle damage. It is known that CK has a high biologic range of response; therefore, the CK non-significant result may be due to the small number of subjects. As no differences were found for AST, liver damage can be excluded. Regarding the results for CRP, probably there is a need for a more specific inflammatory biomarker.